2013
DOI: 10.2308/ajpt-50449
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Evidence Strength and Internal Rewards on Intentions to Report Fraud in the Dodd-Frank Regulatory Environment

Abstract: SUMMARY: There are many unanswered questions and concerns regarding the consequences of the fraud whistleblowing environment created by the Sarbanes-Oxley (SOX) and Dodd-Frank Acts. While SOX requires audit committees to implement anonymous internal reporting channels, the Dodd-Frank Act offers substantial monetary incentives that encourage reporting to the Securities and Exchange Commission (SEC). To mitigate concerns that employees might bypass internal channels, some companies are considering… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
46
0
5

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(59 citation statements)
references
References 32 publications
8
46
0
5
Order By: Relevance
“…For example, Miceli et al () maintained that monetary payouts to whistleblowers could increase internal whistleblowing in terms of its intention and its frequency. Brink, Lowe, and Victoravich () found that monetary rewards for internal whistleblowing increase the intention to use internal channels to report wrongdoing as they replace the role of morality as an intrinsic motivator in the decision whether or not to blow the whistle. Keil et al () also reported that “benefit‐to‐cost differential” creates the intention to blow the whistle.…”
Section: Findings and Discussionmentioning
confidence: 99%
“…For example, Miceli et al () maintained that monetary payouts to whistleblowers could increase internal whistleblowing in terms of its intention and its frequency. Brink, Lowe, and Victoravich () found that monetary rewards for internal whistleblowing increase the intention to use internal channels to report wrongdoing as they replace the role of morality as an intrinsic motivator in the decision whether or not to blow the whistle. Keil et al () also reported that “benefit‐to‐cost differential” creates the intention to blow the whistle.…”
Section: Findings and Discussionmentioning
confidence: 99%
“…Sarbanes-Oxley Act of 2002 requires public companies to have an anonymous reporting channel to record whistleblowers issues; however, this act does not specify how the reporting channel should be administered. Several studies have examined the effect of reporting channel anonymity (Brink et al, 2013;Curtis and Taylor, 2009;Kaplan and Schultz, 2007). Laws and regulations regarding reporting channel would have significant influence in the developing world.…”
Section: Development Of Hypotheses and Empirical Evidencementioning
confidence: 99%
“…The climate of an organisation is influenced by many factors such as the ethical environment, internal rewards and organisation response to prior whistleblowing incidents (Gao and Brink, 2017). Increasing internal rewards increases reporting to SEC (Brink et al, 2013). If the organisation has a history of taking swift actions against ethical violations and fraudulent activities, then employees are more likely to report ethical violations and fraudulent activities (Taylor and Curtis, 2013).…”
Section: Development Of Hypotheses and Empirical Evidencementioning
confidence: 99%
“…We contacted a management representative for each company directly, and 951 companies agreed to participate in the study. (2010) and Brink et al (2013), who find that employees are more likely to report concerns over earnings quality internally, rather than externally. Note also that the standard deviations for reporting via a hotline or externally are more than twice the magnitude of reporting internally, indicating less consensus amongst managers regarding these two reporting options.…”
Section: Participantsmentioning
confidence: 99%